2019
DOI: 10.15171/jhp.2019.11
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of ivy leaf extract on paracetamol-induced oxidative stress and nephrotoxicity in mice

Abstract: Results demonstrate that ivy leaf extract might be used to prevent renal damage induced by paracetamol. This is a promising result for preparation of new drugs. Further studies are required to confirm the mechanisms responsible for nephron-protective activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Additionally, renal functional indicators (urea, creatinine, and uric acid) in plasma and urine of diabetic nephrotoxic In rats are increased significantly (p≤ 0.05) (40). Because ivy leaves have a higher concentration of phytochemicals such flavones, phenolic compounds, Bglycan, and phytosterols, feeding them extract led to lower serum uric acid and creatinine levels (41). In comparison to the paracetamol group, treatment with ivy leaf extract significantly reduced serum concentrations of creatinine, uric acid, and BUN (42).…”
Section: Resultsmentioning
confidence: 95%
“…Additionally, renal functional indicators (urea, creatinine, and uric acid) in plasma and urine of diabetic nephrotoxic In rats are increased significantly (p≤ 0.05) (40). Because ivy leaves have a higher concentration of phytochemicals such flavones, phenolic compounds, Bglycan, and phytosterols, feeding them extract led to lower serum uric acid and creatinine levels (41). In comparison to the paracetamol group, treatment with ivy leaf extract significantly reduced serum concentrations of creatinine, uric acid, and BUN (42).…”
Section: Resultsmentioning
confidence: 95%
“…97 Furthermore, Moshaie-Nezhad et al proposed that CI extracts could prevent paracetamol-induced renal damage in mice, as significant reductions in blood urea nitrogen, creatinine, and uric acid levels were observed in the kidneys of treated mice. 98 Lastly, the flavonoid fraction of the ethanolic ivy extract would be a suitable candidate for treating rheumatoid arthritis (RA). The total ivy ethanolic extract and its isolated flavonoids fraction significantly (p-value <0.05) repressed the biochemical, pathological, and oxidative changes in rats caused by RA.…”
Section: ■ Physicochemical Properties Of CI Biomassmentioning
confidence: 99%
“…Hence, establishing their neuroprotective capabilities makes them interesting candidates to modulate Parkinson’s and Huntington’s disease . Furthermore, Moshaie-Nezhad et al proposed that CI extracts could prevent paracetamol-induced renal damage in mice, as significant reductions in blood urea nitrogen, creatinine, and uric acid levels were observed in the kidneys of treated mice . Lastly, the flavonoid fraction of the ethanolic ivy extract would be a suitable candidate for treating rheumatoid arthritis (RA).…”
Section: Common Ivy Extractives and Their Applicationsmentioning
confidence: 99%
“…Many studies have also reported increased levels of creatinine and blood urea nitrogen (BUN) after APAP toxicity [25][26][27]. These outcomes are potential indicators of nephrotoxicity.…”
Section: Introductionmentioning
confidence: 99%